Pedagogiczne doświadczenie wolności - Marek Kościelniak (Jesuit University Ignatianum in Krakow, 2017)
In students' opinion our schools seem to be institutions governed by constraint. Small spaces of freedom are present in secondary domains of school life and have little to do with its principal domain - teaching and learning. Does it have to be so? It is a serious problem not only to the educational practice, but also to the pedagogical theory. Like Carl R. Rogers, we can look at freedom through the lens of pedagogical experience and see that it dwells at the very heart of the process of "becoming a person". Analysing our experience of personal growth we can see that growth is freedom itself; the processes of becoming are the core manifestation of "inner", personal freedom. This is the way freedom is experien ced by learners and teachers in the process of "signiﬁ cant learning".  The problem is to give a coherent theory to such experience of freedom. Rogers' and other humanistic pedagogues' theories are not satisfactory. They say a lot about students' freedom in educational processes but they disregard the freedom of the teacher.  Martin Buber's model of pedagogical relationship is one in which the freedom of the student and the freedom of the teacher can be realised in perfect (theoretical) harmony. This model is successful thanks to his original explanation of the nature of freedom in relation to responsibility. Responsability itself can be viewed in two contexts; interhuman (ethics) and absolute (values). The teacher has to co-ordinate his responsibility to his pupil with his personal responsibility to God. It is possible.